Electrocatalytic dinitrogen reduction reaction on silicon carbide: a density functional theory study. Issue 38 (22nd September 2020) - Guo, Zhongyuan; Qiu, Siyao; Li, Huan; Xu, Yongjun; Langford, Steven J.; Sun, Chenghua
Abstract : C-SiC offers an ultralow over-potential of 0.39 V for nitrogen fixation, being lower than most metals and alloys. Abstract : It is challenging to identify effective electrocatalysts for nitrogen reduction in order to advance electrochemical nitrogen fixation under ambient conditions using methods that are powered by renewable energy. Silicon carbide was investigated computationally as a metal-free, surface-derived catalyst for the electrocatalytic nitrogen reduction reaction. As demonstrated by first-principle calculations, Si-terminated and C-terminated surfaces, with the Si and C as active sites, are all reactive for dinitrogen capture and activation, resembling the catalytic behavior of popular B-based electrocatalysts, but the latter (C-terminated) offers an ultralow over-potential of 0.39 V, which is lower than most metals and alloys, while retarding hydrogen evolution. This research enriches the design of catalysts for dinitrogen fixation under ambient conditions, and also highlights a new direction for Si-based materials for nitrogen reduction.